Application of complete denture in clas II and class III jaw relationship: Application of complete denture in clas II and class III jaw relationship - Bahruddin Thalib; Rizkiani Awaliyah Ramli (Makassar Dental Journal PDGI Makassar, 2024)
Edentulous patients with class II and class III jaw relationships require modifications in management. This jaw relationship is close-ly related to the fabrication of artificial teeth in a complete denture. The relation of the mandible to the maxilla and cranium is very important in GTL treatment as there are no remaining teeth. This literature review discusses the concept of occlusion used in class II and class III jaw relationships, namely lingual occlusion, which is an attempt to maintain aesthetics with the advantage of anatomical shape while maintaining mechanical freedom in non-anatomical shapes. The use of anatomical artificial teeth in the upper jaw and modified with non-anatomical and semi-anatomical artificial teeth in the lower jaw. It is concluded that good skills and knowledge are needed in treating to replace tooth loss and tissue structure, the success of complete denture treatment of class II and class III jaw relationships can be achieved by paying attention to harmonious denture occlusion.